2011
DOI: 10.1080/09593330.2010.547874
|View full text |Cite
|
Sign up to set email alerts
|

Early warning signs of bulking in an activated sludge system through interpretation of ATP data in a systems analysis context

Abstract: A research project was undertaken at an integrated thermomechanical pulp and paper mill in Canada to evaluate the use of adenosine triphosphate (ATP) monitoring methods in order to identify the potential for operational problems related to microbiological aspects of activated sludge. The specific filamentous bulking ATP (fbATP) ratio is an emerging measurement technique that measures the proportion of flocs that have bulking potential by filtering a sample through a 250 microm mesh and measuring the ATP in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In their study ATP based determinations (used on the basis of 1 fg of ATP/cell) and quantitative PCR (see below) were in good agreement, whilst conventional serial dilution greatly underestimated the populations. A related test kit has also successfully been used for the early warning of activated sludge bulking/foaming (Brault et al, 2011).…”
Section: Adenosine-5'-triphosphate (Atp)mentioning
confidence: 99%
“…In their study ATP based determinations (used on the basis of 1 fg of ATP/cell) and quantitative PCR (see below) were in good agreement, whilst conventional serial dilution greatly underestimated the populations. A related test kit has also successfully been used for the early warning of activated sludge bulking/foaming (Brault et al, 2011).…”
Section: Adenosine-5'-triphosphate (Atp)mentioning
confidence: 99%
“…The importance and criteria of effective monitoring approaches In 2000, a survey conducted by the Water Environment Research Foundation (WERF, Alexandria, VA) showed that 70% of utility respondents experienced WWTP upsets due to influent changes on a regular basis; that 83% of the respondents believed that early warning systems were needed and useful but that 50% did not use these for practical reasons (Love and Bott 2000). Eighteen years later, the lack of efficient, quick, and cost-effective methods to predict process upsets due to influent, environmental, or toxicity changes continues to affect the industry (Archibald and Young 2004;Brault et al 2011;Kapoor et al 2016a;Kapoor et al 2016b;Kungolos 2005;Ren 2004;Ren and Frymier 2006;Xiao et al 2015). Studies have emphasized that any monitoring technologies adoptable by the wastewater industry must be simple, easy to operate and maintain, quick to support operational decision-making, inexpensive, transferable online, and able to predict process changes and upsets (Mamais et al 2008).…”
Section: Monitoring Options For Wastewater Treatment Plantsmentioning
confidence: 99%
“…The use of ATP monitoring has been widely accepted in drinking water due to test sensitive and low detection limits (Hammes et al 2010;Liu et al 2018;Ochromowicz and Hoekstra 2005). Authors have recommended the use of ATP testing for monitoring activated sludge health (F. Archibald and Young 2004;Frederick Archibald et al 2001;Brault et al 2011;Levin et al 1975;Ren 2004;Ren and Frymier 2006). The wastewater industry has been slow to adopt ATP testing due to difficulties in result interpretation and cost but this technique presents much promise.…”
Section: Adenosine Triphosphate Monitoringmentioning
confidence: 99%
“…In general, filamentous bacteria are slow-growing compared to floc-forming bacteria [7]. The most common factors promoting the growth of filamentous bacteria are limitations in substrate (carbon, nitrogen and oxygen) and phosphorous and low concentrations of dissolved oxygen in the ASP [6,[8][9][10][11]. In addition, low temperatures enhance the growth of filamentous bacteria [12].…”
mentioning
confidence: 99%
“…However, Wilén et al [15] found seasonal variations measured as effluent suspended solids (SS) and chemical oxygen demand (COD) concentrations and that in summer, purification generally improved. Thus, the differences among studies might be because SVI is a non-specific measurement and its normal range of values varies in every WWTP [8,17]. In addition, SVI is not a straightforward measurement, as various flocculation abnormalities affect SVI measurement in various ways [18,19].…”
mentioning
confidence: 99%